Scaling the scene: experimental music in Taiwan. Issue 1 (2nd January 2021) - de Seta, Gabriele
ABSTRACT: This article draws on three years of participation in the Taiwanese experimental music scene and argues that, in order to explain how different forms of sociality contribute to its construction and scaling, it is necessary to examine how musicians, organizers and audiences describe their own creative practices. After sketching a brief history of experimental music in Taiwan and contextualizing my positioning as an audience member, musician and critic, I discuss three central components of a music scene: genre, space, and circulation. By analysing the ideological, spatial and material shifts taking place around the Taiwanese experimental music scene in the late 2010s, I demonstrate how musical genres, performance spaces and material circuits are scaled up or down to specific domains of practice or to inclusive social contexts. In this article's conclusion, I revisit scholarship on the concept of music scene and connect it to the role of scaling in the construction of Taiwan's experimental music underground.